CPEC AS A SOCIOECONOMIC STABILITY: THE VIEW OF BALOCHISTAN FUTURE (Contemporary Journal of Social Science Review, 2024)
This research examines how CPEC can spur social advancement, infrastructure development, and economic expansion in Balochistan, Balochistan's sociopolitical environment, which is marked by long-standing complaints about political autonomy and resource distribution, calls for a cautious and inclusive approach to CPEC implementation.It is essential to involve local populations, solve security issues, and make sure that development projects don't make already-existing disparities worse. By using a mixed-methods approach, this methodology seeks to offer a thorough examination of the socioeconomic effects of CPEC on Balochistan. Through the analysis of quantitative data and qualitative insights, this study provide important information regarding the ways in which CPEC affects employment, social stability, and economic growth in the province. The results  form the basis for policy suggestions aimed at optimising the advantages of CPEC for the future of Balochistan.Strong governance, openness in project execution, and the active participation of regional stakeholders are essential for this change. In addition to supporting the larger objective of regional growth and integration within Pakistan, CPEC has the potential to bring about a period of socioeconomic stability and prosperity for Balochistan if it is handled well.In conclusion, even if CPEC offers Balochistan a lot of chances for socioeconomic advancement, resolving the underlying socio-political and economic issues is necessary to reach the project's full potential. CPEC can serve as a pillar for long-term stability and growth in Balochistan by promoting an inclusive development model, thereby establishing a standard for sustainable development in comparable areas.